Investigation of the ex vivo and in vivo iontophoretic delivery of aceclofenac from topical gels in Albino rats - Bhatt, Bhavik; Koland, Marina; Shama, K Prasanna (International Journal of Pharmaceutical Investigation, 2013)
Introduction: Iontophoresis was used to enhance the delivery of aceclofenac (ACF) from topical gels formulated with various polymers for the purpose of relieving pain and inflammation. Materials and Methods: Gels were formulated from hydroxypropyl methyl cellulose (HPMC), carbopol 934P, and sodium carboxymethyl cellulose (NaCMC). The formulations were evaluated for cathodal iontophoretic delivery of ACF through excised rat abdominal skin at three levels of current density of 0.5, 0.6 and 0.7 mA/cm2. The in vivo effectiveness of the drug delivered passively as well as under the influence of iontophoresis at pH 7.4 at a current density of 0.5 mA/cm2 was also investigated using male Albino rats with carrageenan induced paw edema. Results and Discussion: In the ex vivo studies, though it was clear that iontophoresis significantly increased drug permeation through the excised skin from all formulations; the percentage drug permeated from HPMC gels was superior to that from carbopol 934P or NaCMC gels but increased with an increase in the current density only for the former. The steady state flux, permeability coefficient, enhancement factor were significantly greater from HPMC gels than from the gels of the ionic polymers due to the interference of competitive ions. With iontophoresis, the carrageenan induced paw edema was significantly reduced by 61.53% (P < 0.01) for HPMC gels as compared to the control although passive permeation without iontophoresis showed a 54.6% reduction (P < 0.05) at the end of 4 h. Conclusion: The results of the study indicate that ACF could be administered topically by using iontophoresis from a suitably formulated gel for effective control of pain and inflammation.
Keywords: Aceclofenac; drug permeation; gels; iontophoresis